Richardia brasiliensis Gomes: composição fitoquímica, atividade biológica e toxicidade - Dornelles, Rafaela Castro (2022)
Medicinal plants are used both in chemoprevention and in the treatment of a disease after it has already been installed. In general, despite the wide use, knowledge about the phytochemical composition, biological activities, toxicity and mechanisms of action are still poorly explored. In this context, Richardia brasiliensis Gomes (Rubiaceae), it is known as “poaia-branca”, found in practically all continents, appearing in Brazil mainly in regions where there are agricultural activities. It is popularly used in the treatment of diabetes, hemorrhoids, eczema, burns, among others. Despite this, few data regarding its phytochemical constitution and its pharmacological action were found. Thus, the aim of this study was to identify bioactive compounds present in the extracts, through different chromatographic methods; to determine the antioxidant capacity in vitro, using the DPPH, antihemolysis and ORAC assays; to evaluate oxidative parameters such as TBARS, ROS and NO; genotoxic and cytotoxic such as cell viability by the MTT method, double-stranded DNA quantification by the PicoGreen® assay and single-stranded by the Comet DNA method in leukocyte and PBMCs. Besides to analyze the antiproliferative capacity in different tumoral (A375, MCF-7, HeLa, HT-29 and U87) and no-tumor (3T3) cell lines, and to perform acute and repeated dose toxicity analyses in an animal model, following OECD protocols. In the phytochemical screening, the following were identified: anthocyanin heterosides, gums, mucilages, tannins, amino groups, steroids and/or triterpenes, alkaloids, phenols, coumarins, organic acids and flavonoids. Through the different chromatographic methods used, fourteen polyphenols were identified, highlighting the presence of rutin and chlorogenic acid. Alkaloids and terpenes were also secondary metabolism compounds highlighted in both aerial and root extracts. In the determination of metabolites, there was a difference in the different seasons, with the highest concentrations of total polyphenols occurring in spring extracts, flavonoids in autumn, but without differing from winter and spring, and tannins were found in high concentrations in summer. When the extracts were submitted to the evaluation of the antioxidant capacity, the responses were different in the methods used, showing a pronounced antioxidant effect in the anti-hemolysis and ORAC assays. Regarding the oxidative, genotoxic and cytotoxic parameters, there were some changes, especially at higher concentrations. In the evaluation of the antiproliferative capacity, the extract of R. brasiliensis was promising, reducing cell viability by about 95% in human melanoma cells (A375) and it was observed that the phytochemicals present in the extract were able to activate mechanisms that led the cells to apoptosis. In the acute oral toxicity test and in repeated doses, there was no mortality and the animals did not show signs of toxicity during the treatment period. The changes in hematological and biochemical parameters found are within the standards for the species. Thus, the results obtained showed the main substances of secondary plant metabolism responsible for the biological activities attributed to the species R. brasiliensis, demonstrating that the extracts are effective against tumor cell lines, with greater effectiveness against A375. However, under conditions in which the research was performed, the extracts showed some alterations that may be indicating a certain degree of in vitro toxicity in leukocyte cells and in PBMCs. Moreover, in vivo tests suggest that the species is safe for use by the population, however, more long-term toxicity studies are needed to confirm these data.